Identification of Blood Types of Biology Education Students at Samudra University - Dwi Syaravicena; Sri Jayanthi; Aini Ramadila; Suci Nurlida Sapitri; Viska Annisa; Cut Salsabila Mentiasari (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
There are differences on the surface of red blood cell membranes in the types of carbohydrates and proteins that make a person's blood unique, known as blood types. Blood grouping using the ABO system is determined by the absence of antigen A or antigen B in the blood. The presence of A antibodies or B antibodies in red blood cells and serum/plasma. This research was conducted at the Biology Education Research Program, FKIP, Samudra University. This research was conducted from 14 to 24 November 2023. This type of research was qualitative with the slide test method. The parameters observed were the types of blood groups in various samples of 30 students. The results of this study showed that there were more O+ blood types compared to the others, O+ got 46.6% while the others, such as blood type A, were only 16.6% of 30 samples, blood group B was only 33.3% of 30 samples and the last one was the highest. The small number, namely blood type AB+, only reached 3.33% of 30 samples.